Agreement between a new fully automatic ocular biometer based on optical low-coherence reflectometry and an optical biometer based on Scheimpflug imaging combined with partial coherence interferometry - Rui Ning; Huilin Xu; Zheng Li; Jinjin Yu; Shuoyu Xu; Chak Seng Lei; Yiran Wang; Giacomo Savini; Domenico Schiano-Lomoriello; Xingtao Zhou; Jinhai Huang (BMC Ophthalmology, 2024)
Abstract Background To analyze the difference and agreement between measurements obtained by a new fully automatic optical biometer, the SW-9000 μm Plus, based on optical low-coherence reflectometry (OLCR) and a commonly used optical biometer (Pentacam AXL) based on Scheimpflug imaging with partial coherence interferometry (PCI). Methods The central corneal thickness (CCT), anterior chamber depth (ACD, from epithelium to anterior lens surface), lens thickness (LT), mean keratometry (Km), corneal astigmatism, corneal diameter (CD), pupil diameter (PD), and axial length (AL) of 74 eyes (from 74 healthy subjects) were measured using the SW-9000 μm Plus and the Pentacam AXL to determine the agreement. Double angle plots were used for astigmatism vector analysis. Bland–Altman and 95% limits of agreement (LoA) were calculated. Results Statistically significant differences were detected for all parameters but J0 vector. The Bland–Altman analysis of AL, CCT, ACD, Km, CD, J0 and J45 indicated a high level of agreement between the two devices. Among AL, CCT, ACD, Km, J0, J45, CD, and PD, the 95% LoA ranged from  -0.07 to 0.05 mm, -9.67 to 7.34 mm, -0.11 to 0.04 mm, -0.25 to 0.50 D, -0.22 to 0.20 D, -0.15 to 0.20 D, -0.23 to 0.35 mm and 1.55 to 3.77 mm, respectively. Conclusions The measurements of AL, CCT, ACD, Km, corneal astigmatism, and CD showed a narrow LoA and may be used interchangeably in healthy subjects between the new OLCR optical biometer and the Scheimpflug/PCI biometer; however, a poor agreement was noted for PD values.